Nivolumab Versus Sorafenib as First-Line Therapy for Advanced Hepatocellular Carcinoma: A Cost-Effectiveness Analysis - Li, Yan; Liang, Xueyan; Li, Huijuan; Yang, Tong; Guo, Sitong; Chen, Xiaoyu (Frontiers in Pharmacology, 2022)
Objective: Nivolumab improves overall survival (OS) and is associated with fewer adverse events than sorafenib for the treatment of advanced hepatocellular carcinoma (aHCC). However, the cost-effectiveness of nivolumab versus sorafenib treatment for aHCC remains unclear. This study evaluated the cost-effectiveness of nivolumab and sorafenib in the treatment of aHCC. Materials and methods: A partitioned survival model that included three mutually exclusive health states was used to evaluate the cost-effectiveness of nivolumab and sorafenib for treating aHCC. The clinical characteristics and outcomes of the patients in the model were obtained from the CheckMate 459. We performed deterministic one-way sensitivity and probabilistic sensitivity analyses to evaluate the robustness of the model. Subgroup analyses were also performed. Costs, life-years, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefits (INHB), and incremental net monetary benefits (INMB) were measured. Results: The base case analysis showed that, compared with sorafenib, treatment with nivolumab was associated with an incremental of 0.50 (2.45 vs. 1.95) life-years and an incremental of 0.32 (1.59 vs. 1.27) QALYs, as well as $69,762 increment per patient of cost. The ICER was $220,864/QALY. The INHB and INMB were -0.15 QALYs and -$22,362 at a willingness-to-pay (WTP) threshold of $150,000/QALY, respectively. The probabilistic sensitivity analysis demonstrated that the probability of nivolumab being cost-effective was only 10.38% at a WTP threshold of $150,000/QALY. The model was most sensitive to the costs of sorafenib and nivolumab according to the one-way sensitivity analysis. When the price of sorafenib exceeded $0.93/mg or nivolumab was less than $24.23/mg, nivolumab was cost-effective. The subgroup analysis illustrated that the probability of cost-effectiveness was > 50% in the Barcelona Clinic Liver Cancer Stage B subgroups for nivolumab at a WTP threshold of $150,000/QALY. This study also showed that the probability of cost-effectiveness was < 50% in most subgroups. Conclusion: Nivolumab was not cost-effective, although it was associated with clinical benefit and a favorable safety profile for the treatment of aHCC compared with sorafenib from the third-party payer perspective in the United States. If the price of nivolumab is substantially reduced, favorable cost-effectiveness can be achieved among patients with aHCC.